Crystal structure, NMR and theoretical investigations on 2-(o-hydroxy-anilino)-1,4-napthoquinone - Feizi, Nourollah; Pinjari, Rahul V.; Gejji, Shridhar P.; Sayyed, Fareed B.; Gonnade, Rajesh G.; Rane, Sandhya Y. (Journal of Molecular Structure, 2010)
Crystal structure, (1)H NMR and cyclic voltammetric investigations of 2-(o-hydroxy-anilino)-1,4-napthoquinone (HAN), resulting from coupling of aminophenol with 2-hydroxy-1,4-napthoquinone, have been carried out. X-ray structure reveals that the HAN ligand crystallizes in orthorhombic space group Pca2(1) with Z = 4. forming a chain via inter-molecular O2 center dot center dot center dot H1A-O1 and C15-H15 center dot center dot center dot O3 interactions. Both (1)H NMR and cyclic voltammetry experiments suggest the titled ligand is associated and exists as dinner in d(6)-DMSO while the monomer has been predicted in CDCl(3) solution. Density functional calculations can be utilized to gauge the strength of hydrogen-bonded interactions from the (1)H chemical shifts in the NMR spectra. Self-consistent reaction field (SCRF) calculations further support the inferences drawn from cyclic voltammetry experiments. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: (1)H NMR; cyclic voltammetry; Density functional; hydrogen bonding; Napthoquinone